THE APPLICATION OF GUESSING STRATEGY TO IMPROVE STUDENTS’ VOCABULARY MASTERY ON ENGLISH PHRASAL VERBS - ANNA STASYA PRIMA SARI; Siska Ria Pandiangan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2021)
This Classroom Action Research (henceforth, CAR) is mainly aimed at proving that the application of Guessing strategy is able to improve the students’ vocabulary mastery on English phrasal verbs. This CAR was performed in two cycles in which each cycle consisted of three meetings excluded the pre-test, formative test, and post-test. The subjects of this CAR are the fourth semester students of English Language Education Study Program, Faculty of Teachers Training and Education, Catholic University of Saint Thomas in the Academic Year of 2019/2020. There are 20 students as the research subjects. The quantitative data analysis shows that the mean of the students’ score in the pre-test, formative test, and post-test increases significantly after Guessing strategy was applied in the learning teaching processes of English phrasal verbs. The students’ total score of the pre-test is 1.316 and the pre-test mean is 65,8. The students’ total score of the formative test is 1.384 and the formative test mean is 69,2. The students’ total score of the post-test is 1.600 and the post-test mean is 80. There are 8 (eight) students (40%) who attained score >75 in the pre-test, 8 (eight) students (40%) who attained score >75 in the formative test, and 15 (fifteen) students (75%) who attained score >75 in the post-test. The qualitative data analysis shows that the students are more active and enthusiastic in learning and mastering English phrasal verbs after Guessing strategy was applied. Their responses towards the application of Guessing strategy in the learning teaching processes of English phrasal verbs are very positive. All of them agree that learning English phrasal verbs through the application of Guessing strategy can trigger their curiosity and improve their knowledge and vocabulary mastery on English phrasal verbs. The researchers recommend that English learners implement Guessing strategy to improve their vocabulary mastery on English phrasal verbs.